Biocapacity and cost-effectiveness benefits of increased peatland restoration in Scotland. (15th March 2022) - Horsburgh, Nicola; Tyler, Andrew; Mathieson, Scot; Wackernagel, Mathis; Lin, David
Abstract: Ecological Footprint and biocapacity accounting is a widely-used ecological accounting framework which tracks human demand against the biosphere's rate of regeneration. However, current national assessments do not yet include carbon-dense peatlands, hindering the evaluation of peatland biocapacity contributions. Also, the economic efficiency of peatland restoration is understudied and needed to inform land use decisions. We provide the first assessment of Scotland's biocapacity and add peatlands as a novel land type. We then project the biocapacity impacts in 2050 of current peatland restoration targets and various alternative management scenarios. Finally, we estimate the cost per tonne of greenhouse gas abated of various peatland restoration scenarios, and compare this with estimates of afforestation mitigation costs from the literature. Our results show that Scotland's per-person biocapacity exceeds the UK average by a factor of three. However, despite covering 25% of land area, peatland biocapacity increases Scotland's biocapacity total by only 2%, while the Carbon Footprint of degraded peatlands increases Scotland's ecological deficit by 40%. Current peatland restoration targets of the Scottish Government are estimated to reduce the national ecological deficit by only 9% in 2050. The cost-effectiveness of peatland restoration is context-dependent, and extremely cost-effective methods are applicable to peatland areas far exceeding current government restoration targets. Our findings provide land managers with evidence in favour of increased peatland restoration, both in terms of boosting biocapacity, and economic cost-effectiveness. Highlights: First calculation of Scotland's biocapacity, with peatlands as novel land type. Scotland has over three times the UK's average per-person biocapacity. Peatlands contribute only 2% to Scotland's biocapacity due to degradation. Emissions from degraded peatlands increase Scotland's ecological deficit by 40%. Peatland restoration is cost-effective and currently lacks required ambition.